2022
DOI: 10.1088/2632-959x/ac7cfe
|View full text |Cite
|
Sign up to set email alerts
|

Probing into crystallography and morphology properties of MoS2 nanoflowers synthesized via temperature dependent hydrothermal method

Abstract: This paper reports the formation of flower-like hierarchical molybdenum disulfide (MoS2) nanoparticles following a simple one-step hydrothermal process with varying temperatures (200 ⁰C and 220 ⁰C). The as-synthesized particles were examined crystallographically by x-ray diffraction (XRD) method which revealed the formation of hexagonal MoS2 (2H-MoS2). and that the crystallite size of the particles increased with increasing hydrothermal temperature. Surface morphological characteristics of the particles were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The Mo can accelerate the transformation from Fe 7 Se 8 to tetragonal FeSe and the growth of grains by improving atomic diffusion, thus making the sintering process much faster than that in the undoped sample. The layered structure of the two samples that belong to the tetragonal phase is clear and confirms the XRD results with the presence of spherical shapes and flakes related to Fe 7 Se 8 and MoS 2 …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The Mo can accelerate the transformation from Fe 7 Se 8 to tetragonal FeSe and the growth of grains by improving atomic diffusion, thus making the sintering process much faster than that in the undoped sample. The layered structure of the two samples that belong to the tetragonal phase is clear and confirms the XRD results with the presence of spherical shapes and flakes related to Fe 7 Se 8 and MoS 2 …”
Section: Resultssupporting
confidence: 82%
“…This phenomenon results in alterations in the unit cell parameters and atomic arrangements, subsequently leading to shifts in the diffraction pattern. 28 3.2. Thermogravimetric Analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the synthesis method can play a crucial role not only in synthesizing the nanostructures with desired morphology but also in controlling their physiochemical properties. [23][24][25][26][27] Various physical as well as chemical methods can be used to synthesized MoS 2 nanostructures. 28 Depending on the synthesis method, MoS 2 nanostructures can be formed with different morphologies such as 2D sheets, plates, tubes, ribbons, 3D flower, sphere and so on.…”
mentioning
confidence: 99%